1982
DOI: 10.1007/bf00542329
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental passage and breast milk concentrations of hydralazine

Abstract: The concentration of "real" and "apparent" (= "real" hydralazine + acid-labile hydrazones) hydralazine in maternal and umbilical plasma obtained at delivery of 6 women treated with hydralazine and atenolol for pregnancy hypertension were measured by gas chromatography. In one of the patients, the concentrations of the same substances were subsequently measured in breast milk. "Apparent" hydralazine reached higher levels in umbilical than in maternal blood. The concentration of "real" hydralazine seemed to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…In a recent review of progress in this area, Wilson and coworkers (1980) emphasized the lack of quantitative studies of drug distribution in human breast milk. A number of recent and more definitive studies (Findlay et al, 1981a;Liedholm et al, 1981Liedholm et al, , 1982Lonnerholm & Lindstrom, 1982;Steen & Rane, 1982) published on a variety of therapeutic drug types also reflect the rapidly growing awareness that detailed investigation of this field with the use of modern analytical techniques has been neglected until the past several years. Since a variety of drugs may be prescribed for mothers during the period of infant nursing, and because a majority of mothers now breast feed their babies for some period after birth, questions about the safety of nursing the infant while taking medication often arise in pediatric practice.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review of progress in this area, Wilson and coworkers (1980) emphasized the lack of quantitative studies of drug distribution in human breast milk. A number of recent and more definitive studies (Findlay et al, 1981a;Liedholm et al, 1981Liedholm et al, , 1982Lonnerholm & Lindstrom, 1982;Steen & Rane, 1982) published on a variety of therapeutic drug types also reflect the rapidly growing awareness that detailed investigation of this field with the use of modern analytical techniques has been neglected until the past several years. Since a variety of drugs may be prescribed for mothers during the period of infant nursing, and because a majority of mothers now breast feed their babies for some period after birth, questions about the safety of nursing the infant while taking medication often arise in pediatric practice.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of hydralazine exposure during gestation were limited to blood samples collected at the time of delivery or postpartum . These studies demonstrated transplacental fetal exposure to hydralazine, with a mean umbilical cord‐to‐maternal plasma concentration ratio of 2 ± 2.5 at the time of birth.…”
mentioning
confidence: 99%
“…Reserpine may cause some adverse effects in infants (Table 4). [28][29][30][31][32][33][34] β β-BLOCKERS β-Blockers are weak bases and tend to ionize when in breast milk, which is more acidic than plasma. This ionization allows for β-blockers to accumulate in milk.…”
Section: Antihypertensive Agents (Miscellaneous)mentioning
confidence: 99%